An Overview of Resilience in People with HIV/AIDS (PLWHA) at Victory Plus Foundation Yogyakarta - Nawab Husein Siregar (Faculty of Psychology, Universitas Negeri Yogyakarta, 2025)
The process of resilience is important and beneficial for PLWHA. Through the process of resilience, people living with HIV will adapt positively, avoiding various risks such as drug abuse and dangerous sexual activities. Preventing people living with HIV from experiencing these risks is related to improving their health. The purpose of this study was to determine the description of resilience in people with HIV / AIDS at the victory plus Yogyakarta foundation. This study used qualitative research methods with a phenomenological approach conducted at the Victory Plus Foundation Yogyakarta from September to November 2023. Information was obtained using in-depth interview techniques with informants, namely PLWHA. Data analysis used through data reduction, data presentation, and verification stages. The results of the qualitative analysis showed that there was high resilience in people with HIV/AIDS (PLWHA) at the Victory Plus Foundation Yogyakarta. Researchers see the resilience process from various stages, namely personal competence, trusting instincts, through positive acceptance, control, spiritual influence.